The Transformative Value of a Service Experience. (August 2015) - Blocker, Christopher P.; Barrios, Andrés
The pursuit of upward social transformation through service design and practice demands rigorous thinking about what this kind of change looks like and how it comes about. To advance these two goals, this study conceptualizes transformative value, defined as a social dimension of value creation which illuminates uplifting changes among individuals and collectives in the marketplace. Conceptual development draws on structuration theory and the service-dominant logic to articulate the spheres of transformative value as well as four distinctions between habitual and transformative value. Ethnographic analysis with a nonprofit service, which focuses on mitigating the inequalities of poverty, explores how service providers can facilitate transformative value. Findings highlight the roles of holistic value propositions, an anti-structural servicescape, and communal service practices. Beyond micro-level social impact, findings also reveal the macro-level reach of transformative value by demonstrating how services can contest and transform dominant social structures and stimulate social action. Discussion highlights the implications of transformative value for human agency and ways to design services that promote well-being among vulnerable populations.